Impact of Machine Learning on Supply Chain Optimization - Deore, Aakash Ramesh; Shafighi, Najla; Hajibashi, Anahita Amini (Archives of Business Research, 2024)
Supply chain optimization or SCO is the progression that manages the manufacturing industry of Germany and the rate of construction. The study aims to and the consequence of machine learning or ML on SCO of the manufacturing companies in Germany focusing on automobile and Internet of Things (IoT) equipment manufacturing companies. From the study, it will be concluded that the SCO system desires more precision in the supervision system from the employees of the business industry.